Citizen journalism and news objectivity: Issues, challenges and solutions - Ahmad, Sharu Aisha; Abdulrauf, Idris Abdullahi; Joseph, Ayodele Babatunde (Journal of Language, Literature, Social and Cultural Studies, 2024)
The rise of citizen journalism has transformed the media landscape, posing significant challenges to traditional news objectivity. This study aims to investigate the impact of citizen journalism on news objectivity by exploring issues, challenges, and potential solutions. Employing a mixed-methods approach, the research combines qualitative content analysis of citizen-generated news reports with quantitative surveys of professional journalists and citizen journalists. The data collection involved analyzing a sample of news stories from various online platforms and conducting interviews with key stakeholders. Results reveal that while citizen journalism democratizes information dissemination, it often struggles with issues of accuracy and bias, leading to concerns about objectivity. Challenges include the lack of formal training, editorial oversight, and the influence of personal or ideological agendas. However, the study also identifies potential solutions such as promoting media literacy, encouraging collaboration between professional and citizen journalists, and implementing fact-checking mechanisms. In conclusion, while citizen journalism contributes valuable perspectives and diversity to news reporting, addressing its challenges is crucial for maintaining journalistic standards. Ensuring objectivity in this evolving media environment requires a collaborative approach and the integration of rigorous verification processes.